Impact of chemical interface damping on surface plasmon dephasing. (27th February 2019) - Therrien, Andrew J.; Kale, Matthew J.; Yuan, Lin; Zhang, Chao; Halas, Naomi J.; Christopher, Phillip
Abstract : We characterized the change in photon absorption and scattering properties of plasmonic Au nanoparticles by chemical interface damping. Abstract : The excellent light harvesting ability of plasmonic nanoparticles makes them promising materials for a variety of technologies that rely on the conversion of photons to energetic charge carriers. In such applications, including photovoltaics and photocatalysis, the excitation of surface plasmons must induce charge transfer across the metal–adsorbate or metal–semiconductor interface. However, there is currently a lack of molecular level understanding of how the presence of a chemical interface impacts surface plasmon dephasing pathways. Here, we report an approach to quantitatively measure the influence of molecular adsorption on the spectral shape and intensity of the extinction, scattering, and absorption cross-sections for nanostructured plasmonic surfaces. This is demonstrated for the case of thiophenol adsorption on lithographically patterned gold nanodisk arrays. The results show that the formation of a chemical interface between thiophenol and Au causes surface plasmons to decay more prominently through photon absorption rather than photon scattering, as compared to the bare metal. We propose that this effect is a result of the introduction of adsorbate-induced allowable electronic transitions at the interface, which facilitate surface plasmon dephasing via photon absorption. The results suggest that designed chemical interfaces with well-defined electronic structures may enable engineering of hot electron distributions, which could be important for understanding and controlling plasmon-mediated photocatalysis and, more generally, hot carrier transfer processes.